Índice de desenvolvimento sustentável municipal participativo: uma aplicação no município de Cabaceiras-PB - Vasconcelos, Ana Cecília Feitosa de (2011)
In the 90s of last century, simultaneously to the economic globalization process and the strengthening of decentralization policies, the theme of sustainable development arose great interest of the entities worldwide. However, with the progress of discussions on this theme, how to operationalize this concept has become a challenge for governments and society. It is known that the sustainable development of a given location requires a set of actions that should be adopted by local governments together with civil society, which should be the main actor in the planning, execution and control of collective actions, involving different dimensions of citizenship, by creating spaces for interaction among members of the local community. This process is possible only through the involvement and participation of the community in discussions about the need and alternatives, as well as the meeting of consistent indicators and legitimized by local actors. In this perspective, this study aims to identify the index of sustainable development in the city of Cabaceiras - PB including social actors in the weighting and ranking of indicators from the Sustainable Development Index Municipal Participatory. It was used the methodology to calculate the index of municipal participatory sustainable development (IDSMP) proposed by Candido, Vasconcelos and Souza (2010) in the municipality of Cabaceiras - PB. This methodology is the involvement of social actors in the weighting and ranking of sustainability indicators, to identify more effectively the needs of the locality analysis. Thus, the basic premise of the research it was confirmed with the achieved results, since that the more democratic and participatory process for the construction of sustainability indicators, the most reliable will be the information that will enable the sustainable development. In this context, the engagement of social actors in the process of weighting indicators allowed the greater efficiency, effectiveness and legitimacy to the index of sustainable development found, favoring the discussion by society and decision makers who will be ultimately, the real agents of change required to contribute to sustainable development.